Enhancing farmers access to climate information service and climate smart agriculture innovations in Ghana through a multi-channel scaling approach - Obeng Adomaa, Faustina; Mahama, Obed Kwaku; Dalaa, Mustapha Alasan; Tepa-Yotto, Ghislain (2024)
Improving farmers' access to enhanced CIS and validated CSA innovations has been at the core of the Accelerating Impacts of CGAIR Climate Research for Africa (AICCRA) project. This report presents AICCRA Ghana's multi-channel scaling approach that builds on lessons from the first three years of implementation (2021-2023) as a route to scaling access to enhanced CIS and validated CSA to smallholder farmers in Ghana. The report presents CSA hubs as an institutional arrangement for fostering integration and complementarities among multiple channels for scaling site-specific bundled climate solutions to men, women and youth farmers. The report highlights the successes of this integrative scaling approach in reaching over 220,000 new beneficiaries with climate solutions.